Identifying new host-pathogen interactions and developing antivirals against porcine reproductive and respiratory syndrome virus (PRRSV) - Owen, James (The University of Edinburgh, 2024)
Porcine Reproductive and Respiratory Syndrome (PRRS) is a panzootic, viral disease of pigs that persists as a leading cause of losses globally. The etiological agent is the PRRS virus (PRRSV), a rapidly evolving, enveloped, positive-sense RNA virus with a tropism for cells of the myeloid lineage. PRRS can result in reduction or loss of pregnancies, death in young piglets, and decreased growth rates. Modified live vaccines have proven ineffective in curbing the spread of the virus and are not broadly protective. Currently, no small molecule antivirals are available against PRRSV and are an urgent need. Guanylate-binding proteins (GBPs) have been identified as key players in antiviral immunity and host defence against pathogens in a variety of mammalian hosts. Genome-wide association studies have linked porcine GBP1 and 5 with host resistance to PRRSV. Here, we have investigated the functional roles of the complete porcine GBP family, including GBP1, 2, 2L, 5, 6, 6L, and 7 in PRRSV infection. GBPs were differentially upregulated through IFN-γ stimulation and by PRRSV in porcine macrophages. In MARC-145 cells, overexpressed GBPs exhibited differential patterns of expression and localisation, and PRRSV infection influenced localisation of a subset of GBPs. We identified novel phenotypic effects of the GBPs on PRRSV infection, and GBP5 was identified as a potent inhibitor. Further, we have generated a novel porcine cell line by engineering swine testicular cells to express the macrophage receptors CD163 and CD169. Edited cells are fully permissive to both PRRSV-1 and PRRSV-2, and provide new opportunities to validate the phenotypic effects of the GBPs in the presence of endogenous, porcine cellular factors. Additionally, we performed an FDA-approved drug library screen against both species of PRRSV in porcine alveolar macrophages in vitro. We identified 33 potent inhibitors of both PRRSV-1 and PRRSV-2, of which 14 were selected for further validation. These compounds have diverse mechanisms of action and molecular targets, and a number of these have previously been reported to show antiviral activity in vitro. Our results have revealed new therapeutic targets against PRRSV in primary cells, and we have identified promising compounds to be further validated for in vivo testing. Our findings may directly contribute to the rapid repurposing of drugs for the treatment of PRRSV infection.
Keywords: Porcine Reproductive and Respiratory Syndrome (PRRS); Guanylate-binding proteins (GBPs); MARC-145 cells; CD163; CD169; porcine alveolar macrophages